A study of the school resource center management in Sekolah Kebangsaan Padang Jawa, Shah Alam / Ahmad Fuzi Md Ajis - Md Ajis, Ahmad Fuzi (Faculty of Information Management, 2008)
A study of School Resource Center Management in Sekolah Kebangsaan Padang Jawa, Shah Alam is a research focusing on the management of SRC covering the Information Literacy implementation program, Utilization of teaching aids and facilities; and Contribution of the Teacher Librarian to the school. The Information Literacy program implementation is to discover the effectiveness of the IL program that has been implemented in the school. Besides, the understanding of the teachers is also taken into consideration. Utilization of teaching aids focusing on the teaching materials usage in the classroom by the teachers. Contribution of teacher librarian to the school includes the contribution to the students and the teachers. At the end of the study, the finding of the study can act as a guideline in assisting the Teacher Librarian in managing resource center. It also can be used to determine the types of contribution that should be done by a Teacher Librarian.